DOI: 10.22215/etd/2019-13578
|View full text |Cite
|
Sign up to set email alerts
|

Festivals, Festival Foods, and Dietary Acculturation: A Journey of Hybridization and Identity Formation for Chinese International Students in Ottawa

Abstract: Through participant observation at the 2018 Ottawa Night Market Chinatown and interviews with fifteen post-secondary Chinese international students in Ottawa about their dietary acculturation, this research aims to answer the following questions: How does hybridity play out in Chinese students' dietary acculturation? What are the impacts of festivals and festival foods on hybridization and identity formation? The findings suggest that Chinese students do become more "hybrid" in their food practices, but this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
(287 reference statements)
1
2
0
Order By: Relevance
“…This compromise was particularly challenging for students like Ankit (male, community college), who felt that he was "forced to be with other Desis" in distant ethnic enclaves, and in most cases, this resulted in significantly increased commuting time for the students (from home to college to workplaces), thus leaving less time to prepare healthy meals at home. This finding further nuances previous knowledge that even though some international students wish to adopt a "Canadian" lifestyle, they often end up socializing within their own groups (Alotaibi and Lordly 2016;Liu 2019). Our study also found that by living within ethnic enclaves some participants experienced "blocked mobility" (Portes and Zhou 1993).…”
Section: Awareness and Severity Of Food Insecuritysupporting
confidence: 85%
See 1 more Smart Citation
“…This compromise was particularly challenging for students like Ankit (male, community college), who felt that he was "forced to be with other Desis" in distant ethnic enclaves, and in most cases, this resulted in significantly increased commuting time for the students (from home to college to workplaces), thus leaving less time to prepare healthy meals at home. This finding further nuances previous knowledge that even though some international students wish to adopt a "Canadian" lifestyle, they often end up socializing within their own groups (Alotaibi and Lordly 2016;Liu 2019). Our study also found that by living within ethnic enclaves some participants experienced "blocked mobility" (Portes and Zhou 1993).…”
Section: Awareness and Severity Of Food Insecuritysupporting
confidence: 85%
“…In addition to financial precarity, discrimination (i.e., the utilization dimension) often affects international students' consumption of culturally specific foods in their local environments (Liu 2019). While charitable organizations such as "Meal Exchange" have programs to combat student hunger, international students do not have equal access to such programs (Pereira 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the Chinese cuisines in India met with Indian fusion due to non-availability of Chinese ingredients. As claimed by Nandy (2004) and Liu (2019), Chinese food in India came in through the people of China who settled or came in India for studying or for business purpose. As observed by John W.Berry, diasporic people either assimilate completely with the host land, thus losing their identity; they construct an amalgamated identity, thus adopting to hybrid food habits; or they can completely deject themselves from the hostland resulting in preservation of their rooted culture, but this group then undergoes deculturation from the land they live in (Liu, 2019, p.16-17).…”
Section: Indianized Chinese Food Culturementioning
confidence: 99%